History of Criminological Theory - Riyanto, Agung; Sgn, Subhan Zein (Formosa Journal of Sustainable Research, 2024)
Current technological advances have a big impact on social life, social life and mutual respect, so that when we are faced with technological advances but are not balanced by understanding the contents of technology, it will have a negative and positive impact on users and society in general, so there is a need for education about the advantages. and its shortcomings so that we will protect ourselves and society in general from the laws that apply in the country we live in, and especially those of us who live in the Unitary State of the Republic of Indonesia (NKRI)